Variations in Qualitative Traits in the Nigerian Local Chicken - Egahi , J.O.; Dim, N.I.; Momoh, O.M.; Gwaza, D.S. (International Journal of Poultry Science, 2010)
Ninety (90) captive adult normal feathering female Nigerian local chicken in an ongoing study were scored for phenotypic characteristics (variation in plumage and shank colour, presence of ear lobe, ear lobe colour, comb type, head shape and ptilopody). Sole (black, white and light brown) and mottled plumages were dominant and had an occurrence of 54.38 and 38.46% respectively. Shank colour was predominantly black (42.22%). Comb type varied from pea, rose, walnut to single with a percentage occurrence of 18.18, 22.08, 15.58 and 44.16 respectively in the population studied. 82.05% of the population had plain head shape while 70% showed the presence of ear lobes dominated by white colour (73.21%). Ptilopody was observed in 5.41% of the population. The population of Nigerian local chicken studied showed heterogeneity in the phenotypic traits considered and therefore present a genetic pool from which selection could be made.